2011
DOI: 10.1103/physreve.84.036314
|View full text |Cite
|
Sign up to set email alerts
|

Why the water bridge does not collapse

Abstract: In 2007 an interesting phenomenon was discovered: a thread of water, the so-called water bridge (WB), can hang between two glass beakers filled with deionized water if voltage is applied to them. We analyze the available explanations of the WB stability and propose a completely different one: the force that supports the WB is the surface tension of water and the role of electric field is not to allow the WB to reduce its surface energy by means of breaking into separate drops.PACS numbers: 47.55.nk, 47.20.Dr, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Other molecular dynamics simulations have suggested that it is the polarization of hydrogen bonds that induces the formation of the water bridge above a threshold field of 1.2 × 10 9 V∕m (19): which is much higher than the approximately 10 6 V∕m required to form the bridge experimentally. Alternatively, it has been proposed that ordinary surface tension holds the bridge together rather than the electric field directly (20). In this work we have performed high-energy X-ray diffraction experiments, with a submillimeter sized beam, on different parts of the floating water bridge (Fig.…”
mentioning
confidence: 99%
“…Other molecular dynamics simulations have suggested that it is the polarization of hydrogen bonds that induces the formation of the water bridge above a threshold field of 1.2 × 10 9 V∕m (19): which is much higher than the approximately 10 6 V∕m required to form the bridge experimentally. Alternatively, it has been proposed that ordinary surface tension holds the bridge together rather than the electric field directly (20). In this work we have performed high-energy X-ray diffraction experiments, with a submillimeter sized beam, on different parts of the floating water bridge (Fig.…”
mentioning
confidence: 99%
“…The study of this phenomenon was revived by Fuchs et al 2 in 2007. Thereafter, a number of research works [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] have been devoted to the floating water bridges between the deionized water in two containers induced by the high voltages applied to the deionized water. However, the interpretations to the origin of the floating water bridges are different at present stage, 3 for example, dielectric tension, 4 surface tension, 5 or both.…”
Section: Introductionmentioning
confidence: 99%
“…Formal relationships between the physical fluid parameters, electric field intensity, and experimental configuration have been worked out by Marín and Lohse [7] . Aerov [8] on the other hand proposes a model where surface tension is responsible for holding the bridge against the gravity, whereas the electric field assures stability with respect to decomposition into droplets (the Rayleigh-Plateau instability). Woisetschläger et al [9] present a macroscopic theory based on the works of Widom et al [6] and Marín and Lohse [7] .…”
Section: Introductionmentioning
confidence: 99%